How Environmental Factors Affected Escaped Allied Prisoners of War in the Abruzzo and Molise Regions, Italy, 1943 - Heath, Gavin E.C. (Scientia militaria : South African journal of military studies, 2025)
The current study centred on the journey of a party of three Allied prisoners of war (two New Zealanders and one South African), who escaped from the Prigione di Guerra (PG)78/1 camp (henceforth referred to as PG78/1) at Acquafredda near Roccamorice. In this article, the researcher discusses the environmental conditions they faced on their epic journey to British lines near Campobasso. In particular, the bioclimatological factor was examined, as well as other factors, such as river depth, animal presence, and terrain. The literature review employed for the current study comprised memoirs by escaped prisoners of war, popular histories, and recent studies by South African scholars. A mixedmethod methodology was adopted, as meteorological data were obtained from the Italian Meteorological Service (Agenzia ItaliaMeteo, henceforth referred to as “ItaliaMeteo”), from enquiries made to a number of organisations, and during a fieldtrip conducted in the Abruzzo and Molise areas of Italy. The meteorological data provided were excellent; indeed, the study stands by these data. River depth and wildlife were not judged to be major impediments. Enquiries to organisations yielded excellent information, and the fieldtrip provided outstanding context and understanding. It was concluded that the escapees were very fortunate with the timing of the Italian surrender in terms of weather extremes as well as the fact that the local people, the Abruzzesi, went out of their way - at great risk to themselves - to assist the escapees. On the eve of the Italian armistice in early September 1943, the prisoners of war (POWs) interned at Acquafredda (PG78/1), when instructed by their Italian captors to march to the main camp at Sulmona (PG78), instead rebelled, and made a run for it into the mountains. One of those POWs was the author's father, Private George Edward Heath. His war record states that he was a POW from 20 June 1942 until 19 October 1943.2 Heath then escaped together with two New Zealanders (their identities are unknown, and it is not known where exactly they were captured). In the letter, Heath wrote to the Award Publications Ltd in Surrey (applying for the unofficial Prisoner of War Medal),